Solutions to Minimize Project Delays in Civil Construction of High Rise Buildings in the UAE - Baslaib, Mohamed (My University, 2012)
Construction projects of high-rise buildings face different challenges that render projects successful. Project delay, being one of the most significant challenges, can have catastrophic financial and economic consequences on all parties involved in a project including owners, contractors, and consultants. Therefore, this study aspires to investigate the most significant delay factors and rank them according to the perspective of different project stakeholders. The study analyses the importance of delay factors and measures the correlation between the views of different parties involved in high-rise buildings in UAE projects. The second part of the study (capstone two) will investigate best practice solutions for the most significant delay factors found in part one. It will assess the feasibility of implementing such solutions and make recommendations regarding the implementation of such solutions.
Keywords: High Rise Buildings; Project Delays; Construction Economics; Minimization of Cost